Fundamentals of computation theory 18th International Symposium, FCT 2011, Oslo, Norway, August 22-25, 2011. Proceedings - FCT 2011 (2011 Oslo, Norway); Owe, Olaf.; Steffen, Martin; Telle, Jan Arne.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 18th International Symposium Fundamentals of Computation Theory, FCT 2011, held in Oslo, Norway, in August 2011. The 28 revised full papers presented were carefully reviewed and selected from 78 submissions. FCT 2011 focused on algorithms, formal methods, and emerging fields, such as ad hoc, dynamic and evolving systems; algorithmic game theory; computational biology; foundations of cloud computing and ubiquitous systems; and quantum computation.
Electronic reproduction.
Keywords: Computer science -- Congresses; Electronic books